Perhubungan Preferensi Risiko dan Kemiskinan di Indonesia: The Nexus of Risk-Preferences and Poverty in Indonesia - Siti Aisyah Tri Rahayu; Mulyanto Mulyanto; Johadi Johadi; Muhammad Yusuf Indra Purnama (Society, 2023)
This research aims to identify the relationship between poverty and risk preference in Indonesia empirically. This research employs the Indonesia Family Life Survey 2014 (IFLS5) using the Ordinary Least Square (OLS) and quantile regression approach, one of the most extended longitudinal data, to support this research design. The result reveals that poor households are more risk-averse than others across income levels. Moreover, poor people are poorly educated and mostly come from rural and disaster-prone areas. This evidence suggests that poor people from rural communities and disaster-prone regions should be prioritized and empowered to move from poverty zones due to their relatively high vulnerability.